Migración Afroecuatoriana hacia España (1998-2018): análisis de las representaciones sociales y culturales. - Mosquera Castillo, Darlin Nel (2019)
The purpose of the research was to analyze Afro-Ecuadorian migration in Spain, its social and it cultural representation during the period of 1998 - 2018. A qualitative research with a narrative design was used. The applied technique was in-depth interviews of twenty-four Afro-Ecuadorians residing in the cities of Almería, Elche, and Santander. Among the most relevant findings stand out the re-signification of social and cultural representations due to the change of Afro-Ecuadorians’ initial expectations in contrast to what they found upon arrival in Spain. This situation led them to face a process of readjustment, in which the initial social representations were rethought to adapt to the new context and the new reality as Afro-Ecuadorian migrants.